Mind the gap: Ensuring laboratory‐scale testing of an electrospinning product meets commercial‐scale needs. Issue 20 (7th February 2017) - LeCorre‐Bordes, Deborah S.; Jaksons, Peter; Hofman, Kathleen
ABSTRACT: Plant & Food BioProcessing has developed a process to electrospin denatured whole‐chain marine collagen. The collagen is routinely tested on laboratory‐scale electrospinning equipment, but when it is electrospun on industrial equipment, the conditions and the product testing criteria differ from those used in the laboratory. A laboratory electrospinning machine was modified to simulate industrial conditions (≥30 kV). Then, several parameters (voltage, working distance) were adjusted from laboratory‐ to commercial‐scale. These changes did not affect average fiber diameter or deposition rate. The optimum electrospinning conditions were a mixture of laboratory‐ and commercial‐scale conditions (30–50 kV; 10 cm working distance). Reducing the working distance by 5 cm improved the production rate by up to 75%. These changes resulted in better repeatability of electrospun fibers over multiple production runs, with fewer adjustments of solutions and parameters. We recommend this approach to design materials and processes relevant to industrial manufacturing of electrospun fibers. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44836. Abstract :